Challenges And Opportunities Of Community Health Center In Initial Emergency Management Of Patients With Acute Kidney Failure - Astuti Sigalingging, Yulia Emma Wahyu Kristi (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2023)
Acute kidney injury (AKI) is a sudden condition in which kidney function declines drastically, leading to disturbances in fluid balance, electrolyte regulation, and waste excretion. This medical emergency requires immediate intervention as it can result in life-threatening complications. This study discusses the early emergency phase of patients with AKI, focusing on the causes, clinical manifestations, and medical approaches to stabilize patients. Early recognition of AKI is crucial for preventing progression to severe complications such as metabolic acidosis, hyperkalemia, fluid overload, and uremic complications. The abstract highlights key aspects of emergency assessment, including laboratory and imaging evaluations, as well as initial management strategies. Initial treatment involves identifying and addressing underlying causes, fluid resuscitation, electrolyte correction, and determining the need for renal replacement therapy such as emergency dialysis. The role of healthcare professionals is emphasized in providing timely and effective treatment to improve patient outcomes and reduce morbidity and mortality rates. This research aims to provide valuable insights into the early management of AKI emergencies, equipping medical professionals with essential knowledge to optimize patient care and prevent further deterioration. Early management involves identifying and treating the underlying cause, optimizing fluid balance through careful resuscitation, correcting electrolyte imbalances, and assessing the need for renal replacement therapy (such as emergency dialysis). Supportive care, including monitoring for complications like sepsis and cardiovascular instability, is crucial to improving patient outcomes. The role of healthcare professionals is vital in ensuring timely and effective treatment, which can significantly reduce morbidity and mortality associated with AKI. This research aims to provide comprehensive insights into the early emergency management of AKI, equipping medical professionals with essential knowledge to optimize patient care, prevent further deterioration, and improve overall prognosis.